NATIONAL SYSTEM OF TRAFFIC INFORMATION AND BENEFITS FOR ROAD TRAFFIC SAFETY - Kalasova, Alica; Cernicky, Lubomir (Doprava a spoje, 2011)
Recently, there has been a very rapid development of individual car traffic due to rising living standards and continuous improvement of conditions for automobile transport, and therefore, the present transport network ceases to satisfy. However, transport is an integral part of society - without continued transportation of materials, products and information, modern society could not exist. Slovakia has an advantageous geographical position in Central Europe and because of this; it is an important traffic intersection, where road traffic is still dominated as a mode of transport. With increasing intensity and capacity of road traffic, its accompanying negative characters are still more proved and the problems have been associated with the establishment and functioning of the transport system. The paper deals with the issue the national system of traffic information in Slovak republic and his benefits for road traffic safety.